2023
DOI: 10.1007/s40544-022-0686-6
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity by polyimide-induced alignment

Abstract: We have investigated the lubrication alignment behavior of point—plane contact and plane—plane contact between the GCr15 steel and polyimide (PI) friction pair using nematic liquid crystals (LCs) as the lubricant. In this system, rubbing orients the macromolecular PI molecules, and the oriented PI molecules induce alignment of the LC molecules in contact with or close to the oriented PI molecules. The LC molecules are aligned in the wear scar grooves of the PI film, and alignment extends to the GCr15-steel cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Superlubricity provides a viable solution to the negative effects of friction. Superlubricants can be broadly classified into two categories: solid and liquid . For the former, typical ones include molybdenum disulfide, graphene, diamond-like carbon films, and multiwalled carbon nanotubes. However, solid superlubricity materials usually require specific conditions (e.g., vacuum/inert gas atmosphere, incommensurate contact, micrometer size, and absolute surface rigidity) to achieve superlubricity, whereas the liquid ones easily achieve macroscopic superlubricity on routinely flat surfaces under atmospheric conditions such as aqueous phosphoric acid solutions .…”
Section: Introductionmentioning
confidence: 99%
“…Superlubricity provides a viable solution to the negative effects of friction. Superlubricants can be broadly classified into two categories: solid and liquid . For the former, typical ones include molybdenum disulfide, graphene, diamond-like carbon films, and multiwalled carbon nanotubes. However, solid superlubricity materials usually require specific conditions (e.g., vacuum/inert gas atmosphere, incommensurate contact, micrometer size, and absolute surface rigidity) to achieve superlubricity, whereas the liquid ones easily achieve macroscopic superlubricity on routinely flat surfaces under atmospheric conditions such as aqueous phosphoric acid solutions .…”
Section: Introductionmentioning
confidence: 99%
“…The study found that a trilayer frictional film, composed of amorphous carbon, graphene crystals, and phosphorus trioxide, was formed during the friction process. This film supplants the traditional shear interface between steel/steel, leading to macroscopic superlubricity in the frictional process . Other typical superlubricity materials include graphite and graphene materials, molybdenum disulfide (MoS 2 ), , solid nanocomposites, , water, oil-based solutions, polyol solutions, , biological mucus, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This film supplants the traditional shear interface between steel/steel, leading to macroscopic superlubricity in the frictional process. 14 Other typical superlubricity materials include graphite and graphene materials, 15−18 molybdenum disulfide (MoS 2 ), 19,20 solid nanocomposites, 21,22 water, oil-based solutions, 23−25 polyol solutions, 26,27 biological mucus, 28−30 and so on. However, all of these studies were conducted without EEFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is widely recognized that the key to achieving liquid superlubricity is to ensure that the liquid molecules are stabilized on the surface of the friction pair under external pressure while providing very low shear strength [ 34 ]. Through the initial exploration of liquid superlubricity systems, our team also discovered a superlubricity system using nematic liquid crystals (LCs) as the lubricant and GCr15 steel with PI as the friction pair [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we tested a system with a PI film and GCr15 steel as the friction pair and nematic LCs as the lubricant and found that friction led to the alignment of PI, and aligned PI induced the orientation of LCs in the grooves of PI wear scars, resulting in the stable superlubricity property of the system [ 35 , 36 ]. For this type of superlubricity system, the alignment of PI and LCs is very important.…”
Section: Introductionmentioning
confidence: 99%